Role-playing as a CALLA-related metacognitive learning strategy for English vocabulary acquisition in EFL classrooms. - Prieto Gómez, Karen Julieth (Universidad Antonio Nariño, 2024)
The objective of this proposal is to provide an overview of the application of role-playing as a metacognitive learning strategy implemented through CALLA to acquire English vocabulary. The need to create this is because role plays are often carried out where they are used as a metacognitive learning strategy to acquire vocabulary.